Policies for growth : the Latin American experience : proceedings of a conference held in Mangaratiba, Rio de Janeiro, Brazil, March 16-19, 1994 - Resende, André Lara, moderator (IMF Washington, D.C.US, 1995)
Looks at the general characteristics of stabilisation programmes in Latin America. Discusses the distributive and social costs associated with the stabilisation process. Examines the themes of the institutionalo reforms associated with stabilisation.